Occupational skin exposure and hand eczema among dental technicians—need for improved prevention - Meding, Birgitta; Wrangsjö, Karin; Hosseiny, Seiran; Andersson, Eva; Hagberg, Stig; Torén, Kjell; Wass, Kristina; Brisman, Jonas Brisman (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'The aims of this study were to estimate occupational skin exposure, the use of skin protection, and the incidence of hand eczema among dental technicians. ' ' METHODS ': 'In a retrospective cohort study, dental technicians (N=2139) and randomly selected population controls (N=2288) received a postal questionnaire on occupational skin exposure, protective glove use, and hand eczema, including the year of onset. The response rate was 57% for the dental technicians and 58% for the controls. ' ' RESULTS ': 'Altogether 80% of the dental technicians reported skin exposure to uncured (meth)acrylates (MA), and 87% had skin contact with grinding dust from MA. Thirty-nine percent used protective gloves when handling uncured MA. Twenty-two percent of the currently employed technicians reported participation in obligatory training concerning the handling of thermosetting plastics, and 58% did not know how long normally used gloves protected the skin against uncured MA. Altogether 48% of the dental technicians and 30% of the controls reported more than 10 hand washings a day (P
Keywords: (meth)acrylates; dental technician; dermatitis; epidemiology; grinding dust; hand eczema; hand washing; incidence; occupational skin exposure; prevention; protective gloves; work change